2021
DOI: 10.3389/fncel.2021.640724
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Exercise Training Protects the Brain Against Autoimmune Neuroinflammation: Regulation of Microglial Redox and Pro-inflammatory Functions

Abstract: Background: Exercise training induces beneficial effects on neurodegenerative diseases, and specifically on multiple sclerosis (MS) and it’s model experimental autoimmune encephalomyelitis (EAE). However, it is unclear whether exercise training exerts direct protective effects on the central nervous system (CNS), nor are the mechanisms of neuroprotection fully understood. In this study, we investigated the direct neuroprotective effects of high-intensity continuous training (HICT) against the development of au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 58 publications
2
34
0
Order By: Relevance
“…The PLP 139-151 transfer EAE model in mice was utilized as previously described. [2][3][4]17 To assess the modulatory effects of ET on systemic autoimmunity, we examined in vivo and in vitro the encephalitogenicity of lymph nodes cells (LNCs) from mice that underwent the HICT program prior to proteolipid (PLP) immunization, compared with LNCs from sedentary (SED) mice (Fig. 1A).…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The PLP 139-151 transfer EAE model in mice was utilized as previously described. [2][3][4]17 To assess the modulatory effects of ET on systemic autoimmunity, we examined in vivo and in vitro the encephalitogenicity of lymph nodes cells (LNCs) from mice that underwent the HICT program prior to proteolipid (PLP) immunization, compared with LNCs from sedentary (SED) mice (Fig. 1A).…”
Section: Experimental Designmentioning
confidence: 99%
“…Healthy mice underwent 6-wks of HICT treadmill running, including pre-and post-training performance tests on a 5-lane treadmill designed for mice (Panlab Harvard Apparatus, USA) as previously described. 3,4,17…”
Section: Treadmill Exercise Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Microglial activation and population in HPC are reduced following exercise (Kohman et al, 2013 ; Mee-inta et al, 2019 ). High-intensity exercise serves a general neuroprotective role by reducing microglial-associated inflammation (Zaychik et al, 2021 ), which is also associated with increases in BDNF expression and improvements in spatial working memory (Xiong et al, 2015 ). Together, these data highlight how exercise is expected to reverse some of the negative consequences of ELA on glia cell proliferation and function so as to ameliorate behavioral deficits.…”
Section: Targeted Treatment Interventions For Ela Exposure: Preclinical and Clinical Findingsmentioning
confidence: 99%
“…The effect of exercise strongly depends on its modality, intensity, and timing. A recent study investigating the direct effects of highintensity continuous training (HICT) on neuroprotection in the central nervous system (CNS) suggested that HICT protected the CNS against autoimmune neuroinflammation by reducing microglial-derived neurotoxicity, and proinflammatory responses, rather than inducing their shift to M2 phenotype [56]. However, it has also been observed that excessive vigorous exercise still promoted M2 polarization of macrophages in skeletal muscle, and myogenesis increases despite the increase of TNF-α [57].…”
mentioning
confidence: 99%